2019
DOI: 10.3390/jcm8101574
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Study in Vivo for New Pharmacological Approaches in Inflammatory Bowel Disease: A Systematic Review of Chronic Model of TNBS-Induced Colitis

Abstract: The preclinical studies in vivo provide means of characterizing physiologic interactions when our understanding of such processes is insufficient to allow replacement with in vitro systems and play a pivotal role in the development of a novel therapeutic drug cure. Chemically induced colitis models are relatively easy and rapid to develop. The 2,4,6-trinitrobenzenesulfonic acid (TNBS) colitis model is one of the main models in the experimental studies of inflammatory bowel disease (IBD) since inflammation indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 100 publications
2
57
0
3
Order By: Relevance
“…In previous studies, the reversal effect on the pathological process in colitis model has been confirmed through injection of helminth-derived secretory proteins or adoptive transfer of helminth-induced macrophages (66)(67)(68). As a rapid and highly reproducible animal model, the TNBS-induced IBD model is characterized by acute colitis and exhibits a condition similar to Crohn disease (69). In this model, alleviation of pathological inflammatory processes appeared after treatment with rTs-serpin or rTs-serpin-treated BMDMs and was associated with a significant upregulation of anti-inflammatory cytokines, which supported the anti-inflammatory and regulatory effects of rTs-serpin identified previously.…”
Section: Discussionmentioning
confidence: 89%
“…In previous studies, the reversal effect on the pathological process in colitis model has been confirmed through injection of helminth-derived secretory proteins or adoptive transfer of helminth-induced macrophages (66)(67)(68). As a rapid and highly reproducible animal model, the TNBS-induced IBD model is characterized by acute colitis and exhibits a condition similar to Crohn disease (69). In this model, alleviation of pathological inflammatory processes appeared after treatment with rTs-serpin or rTs-serpin-treated BMDMs and was associated with a significant upregulation of anti-inflammatory cytokines, which supported the anti-inflammatory and regulatory effects of rTs-serpin identified previously.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, at week 8 in the experimental schedule, when the administrations of intrarectal TNBS were completed, all the animals belonging to these three groups exhibited some recovery, and their body weights were nearly equal to that of the C− group. These results might be explained by the decreased ability to maintain TNBS-induced colitis in mice older than 8 weeks 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The rats were anaesthetised with 3% pentobarbital sodium (0.15 mL/100 g). A rubber infusion tube was then inserted 8 cm into the upper anus of each rat and injected with 5% TNBS at 100 mg/kg (dissolved in 50% ethanol, total volume of 1 mL) (34,35). To prevent uid leakage after colonic infusion and ensure the induction of colitis, the rats were placed in the Trendlenburg position with their head down for 1 min (36).…”
Section: Discussionmentioning
confidence: 99%